ANALISIS FAKTOR-FAKTOR YANG BERPENGARUH PADA PEMILIHAN METODE DEPRESIASI - Rossje V Suryaputri; Kerala , (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2007)
The main objective of this study is to obtain evidence whether manager choices to the available accounting procedure, especially depreciation methods, is related and affected by some factors such as film size, leverage ratio, and accounting ROA. It was assumed that manager in the small company with high leverage ratio and decreasing trend of accounting ROA preferred to select depreciaffon method which can increase the reported earning by using the straight-line depreciation method. On the contrary, manager in the larger company with low leverage ratio and increasing trend of accounting ROA tend to select depreciation method which can reduce the reported earning by using double declining balance or accelerated depreciation method. This study was conducted by selecting of 121 public fisted manufacturing companies as an object. The finn's size was determined by total assets, while leverage ratio and accounting ROA were measured by the ratio of total liabilities to total assets and ratio of operating profit to average of total assets. The study concludes that there are a positive correlation between leverage ratio and the choice of depreciation method On the contrary, there are no correlation between the firm's size and accounting ROA with the choice of depreciation method. There is an effect of leverage ratio to the selection of depreciation method. On the other hand, there is no effect between the firm size and accounting ROA to the selection of depreciation method.Keywords: Financial Accounting Standard, Depreciation Method